TRANSFORMASI IDENTITAS AKTIVIS GERAKAN ISLAM - Aam Amirudin (Linimasa : Jurnal Ilmu Komunikasi, 2019)
ABSTRACT The aim of this paper examines the phenomenon of process and direction of identity transformations of the Tarbiah movement activists that becomes the activist of political movement. As the qualitative research, the data is achieved by in-depth interview and participatory observation. Fourteen politicians from Tarbiah activists have become the informant for this research. The result shows that identity transformation has been experienced by Tarbiah movement activists. The identity transformation progressively persisted through; open-minded thoughts, enthusiastic effort to the value of universal truth, developing ideological awareness, and become the agent of change. Becoming the political activist has brought them to the positive contemplation through three stages, namely ruhiyyah, fikriah, and amaliah contemplation. There are also positive and progressive changes in the communication with the non-activists. After becoming the parliament member, verbal symbol becomes more flexible and realistic in term of the approach of problem solving. Being a politician has grown the transcendental awareness that this position is a fate, trusteeship, and temptation. In developing a good self-image Tarbiyah activists apply two strategies: Firstly, impression management by using and discarding personal front. Secondly, collaborative teamwork for image management. Those two management strategies are conducted in front of the non-activist apart from their community. Keywords: identity transformation, communication construction, and phenomenology